A study on awareness depositors TH toward wasiyyah practice / Nurul Nadhirah Zakaria - Zakaria, Nurul Nadhirah (2018)
Abstract: The amount of frozen assets due to unclaimed inheritance to the muslim society in Malaysia is significant. There are being about a million land titles that are still in the name of the deceased owners. In 2012, the amount of frozen estates is estimated to be around RM45 billion and this figures is expected to increase further. This tatistics is alarming and calls for an urgent need in solving the problem of unclaimed inheritance to the Muslim society in Malaysia. It is imperative to teach that Muslims have a clear idea about the appropriate instruments and course of actions in estate planning. The majority of Muslims in Malaysia do not view estate planning as a serious matter. This study aim to investigate the level awareness depositors TH towards wasiyyah practice. The objective of this study is to investigate the level awareness of depositors TH towards wasiyyah practice, to identify the relationship between Independent variable (knowledge) and Dependent variable (awareness of wasiyyah practice) and identify the relationship between Independent variable (cultural value) and Dependent variable (awareness of wasiyyah practice). The finding found the level of awareness of depositor TH toward wasiyyah practice is moderate high (mean=3.73). The correlation between knowledge (r=0.335) & cultural value (r=0.404) and awareness of wasiyyah practice is medium strong.